2022
DOI: 10.1002/ael2.20080
|View full text |Cite
|
Sign up to set email alerts
|

Seed size variability has implications for achieving cover cropping goals

Abstract: It is common to use mass-based units (e.g., kg ha -1 ) to describe cover crop seeding rates. However, this convention obscures important information about seed size and resulting plant density in the field, which may be linked to cover crop performance and ecosystem services. Seed counts of 27 lots of commercially available winter rye (Secale cereale L.) spanned a wide range from 28,000 to 50,000 seeds kg -1 . If the lots with the lowest and highest seed counts were seeded at a common mass-based seeding rate o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Similarly, Lounsbury et al. (2022) found that cereal rye seed size varied widely across cultivars, which could result in major differences in plant populations if a mass‐based, rather than density‐based, seeding rate is used. Such differences can also have economically significant ramifications, especially as the price per unit (i.e., bag of seed) can also vary a lot.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Lounsbury et al. (2022) found that cereal rye seed size varied widely across cultivars, which could result in major differences in plant populations if a mass‐based, rather than density‐based, seeding rate is used. Such differences can also have economically significant ramifications, especially as the price per unit (i.e., bag of seed) can also vary a lot.…”
Section: Resultsmentioning
confidence: 99%
“…The mean seed mass for the barley cultivars was 73% and 38%, 76% and 74%, and 37% and 20% greater than the Aroostook cereal rye seed mass for barley, triticale, and the three other cereal rye cultivars in 2014 and 2015, respectively (Table 2). Similarly, Lounsbury et al (2022) found that cereal rye seed size varied widely across cultivars, which could result in major differences in plant populations if a mass-based, rather than density-based, seeding rate is used. Such differences can also have economically significant ramifications, especially as the price per unit (i.e., bag of seed) can also vary a lot.…”
Section: Cover Crop Biomassmentioning
confidence: 99%
“…Winter cereals were drill-planted at a depth of 2.5-3.8 cm with 19-cm row spacing on September 19, 2014, in NY andOctober 2, 2014, in MD. Although some farmers do not prioritize early winter cereal planting dates, these dates were selected due to the importance of fall growing degree days for biomass production in the spring (Mirsky et al, 2009). Earlier fall planting dates are also compatible with the typical harvest Seed size can vary widely across species and even cultivars, leading to potentially large differences in plant populations when using mass-based seeding rates (Lounsbury et al, 2022). To address this issue, all twelve winter cereals were seeded at an equivalent rate based on seed density, with "Aroostook" cereal rye as the reference cultivar.…”
Section: Experimental Design and Field Operationsmentioning
confidence: 99%
“…This seeding rate gradient includes lower rates that are commonly used by growers targeting soil-health management goals and higher rates that are believed to optimize weed suppression potential within low-input systems. Cereal rye seed lots were not subsampled to quantify seed mass (i.e., seeds per kilogram), which constrains our inferences to relative comparisons of seeding rates within site-years, given the potential for variation in seed size that has been observed (Lounsberry et al 2022).…”
Section: Experimental Design and Field Operationsmentioning
confidence: 99%